Emily C. Donaldson, Working with the Ancestors: Mana and Place in the Marquesas Islands. (8th November 2021) - Riley, Kathleen C.
Abstract : Emily C. Donaldson, Working with the Ancestors: Mana and Place in the Marquesas Islands (Seattle: University of Washington Press, 2019), 250 pp., 30.00 (pbk), ISBN: 9780295745831.